Watersport Hands. (July 2014) - Kent, Jeremy B.; Statuta, Siobhan M.; Greer, Kenneth E.; MacKnight, John M.
Aquagenic syringeal acrokeratoderma is a newly described condition of the palms and soles characterized by hypopigmented papules and plaques, elicited after submersion in water. Symptoms include a burning pain and a tightening sensation in the palms, as well as hyperhidrosis. Initially thought to be rare, its frequent citation in the literature points to a more common entity. It is more often found in young women and has been linked to a number of medications and illnesses, including nonsteroidal anti-inflammatory drugs and cystic fibrosis. It is typically self-limiting, but certain medications such as topical aluminum chloride or salicylic acid ointment have been found to be an effective treatment option. This case details a collegiate-level coxswain who presented to the university athletic training room with a typical presentation of aquagenic syringeal acrokeratoderma. For an aquatic athlete, aquagenic syringeal acrokeratoderma can be a distressing condition that can limit training and athletic participation. As such, the sports medicine physician should be knowledgeable about aquagenic syringeal acrokeratoderma to provide effective counseling and treatment options for the athlete.